The Influence of Work Discipline and Work Environment on the Work Performance of Inpatient Nurses at Bhayangkara Hospital, Pontianak - Aziz, Abdul; Meri, Meri; Nuraini, Novia; Supriyadi, Supriyadi (IJBLE Scientific Publications Community Inc., 2024)
This study aims to reveal the influence of work discipline and work environment on the work performance of inpatient nurses at Bhayangkara Hospital, Pontianak. The research design used was non-experimental and used cross-sectional analytics. Data analysis using Logistic Regression. Research data was obtained from valid and reliable research instruments. The population in this study were all inpatient nurses. The research sample was 46 inpatient nurses. Research Results: 1) regression analysis of the influence of work discipline on nurses' work performance, p-value < 0.05, thus there is an influence of work discipline on work performance; 2) the Odds Ratio value is 4.582, meaning that nurses with high work discipline have a 4.582 times chance of having good work performance compared to nurses who have low work discipline; 3) the influence of the work environment on the work performance of nurses obtained p value <0.05. Thus there is an influence of the work environment on the work performance of inpatient nurses; 4) the Odds Ratio value is 2.924, meaning that nurses with a good work environment have a 2.924 times chance of having good work performance compared to nurses who have a poor work environment; 5) The R-Square value is 0.722, meaning that the influence of work discipline and work environment on the work performance of inpatient nurses is 72.2%.